2016
DOI: 10.3389/fmicb.2016.01378
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of ELF-EMF and RF-EMF Increase the Rate of Glucose Transport and TCA Cycle in Budding Yeast

Abstract: In this study, we investigated the transcriptional response to 50 Hz extremely low frequency electromagnetic field (ELF-EMF) and 2.0 GHz radio frequency electromagnetic field (RF-EMF) exposure by Illumina sequencing technology using budding yeast as the model organism. The transcription levels of 28 genes were upregulated and those of four genes were downregulated under ELF-EMF exposure, while the transcription levels of 29 genes were upregulated and those of 24 genes were downregulated under RF-EMF exposure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 40 publications
1
5
1
1
Order By: Relevance
“…This experiment is an exploratory experiment that found some response of cyanobacteria to electromagnetic radiation. Previous studies in our laboratory have found that electromagnetic waves have effects on the energy metabolism of Caenorhabditis elegans 59 , 60 and yeast 61 , which is similar to the results of this experiment. Next, we need to further study the mechanism of electromagnetic radiation's influence on energy metabolism pathway and changes in energy metabolism-related metabolites and so on.…”
Section: Discussionsupporting
confidence: 90%
“…This experiment is an exploratory experiment that found some response of cyanobacteria to electromagnetic radiation. Previous studies in our laboratory have found that electromagnetic waves have effects on the energy metabolism of Caenorhabditis elegans 59 , 60 and yeast 61 , which is similar to the results of this experiment. Next, we need to further study the mechanism of electromagnetic radiation's influence on energy metabolism pathway and changes in energy metabolism-related metabolites and so on.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, despite the fold change detected by mRNA-seq, which was not the same and was generally larger than that obtained by RT-PCR, as reported in a previous study [ 63 ], it was possible to observe, for all the genes analyzed, a similar trend between the results obtained from the two methodologies, in terms of direction of change. The discrepancies between the fold changes observed with the two methods can be related to the differences in the normalization process of data analysis between the two techniques, since the unit of measure is different.…”
Section: Discussioncontrasting
confidence: 55%
“…To the best of our knowledge, only three in vivo studies evaluated the genome-wide mRNA expression profile using the Illumina sequencing technology, reporting differentially expressed genes in Caernorhabditis elegans after prolonged exposure to 1.75 GHz (SAR = 3 W/kg) [ 62 ] and in some genes related to energy metabolism in budding yeast after exposure to 50 Hz and 2.0 GHz [ 63 ]. A more recent study performed on Escherichia coli K-12 DH5α exposed to 2.4 GHz for 5 h reported that most of the genes identified were involved in many cellular and metabolic processes [ 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, the surface temperature of each sample during the exposure period was checked using a thermal imager (Testo 890). All of the monitoring data showed that the temperature of the control and exposure samples remained stable 30 . Experimental exposure device was shown in Fig.…”
Section: Methodsmentioning
confidence: 97%